The influence of macroeconomic conditions and institutional quality on national levels of life satisfaction - Brendan Walsh (University College Dublin, UCD School of Economics, 2012)
Answers to the Eurobarometer question on Life Satisfaction are used to explore the effects of macroeconomic performance and institutional quality on average levels of self-assessed well-being in the countries of the enlarged European Union between 2004 and 2011. It is found that variations in national levels of life satisfaction can largely be accounted by a small number of socio-economic indicators. Life satisfaction is lowest in poor, corrupt countries where income inequality is pronounced. The adverse effect of higher unemployment on life satisfaction is partially offset by the positive impact of lower inflation. However, even when these factors are allowed for, significant country-level differences persist.
Keywords: 330; Life Satisfaction; Living Standards; Unemployment; Inflation; Corruption; Income Inequality